Performance of lightweight SCC beams strengthened with rubberized engineered cementitious composite in shear. (1st February 2022) - Ismail, Mohamed K.; Hassan, Assem A.A.
Highlights: Shear behavior of LWSCC beams strengthened with RECC was studied. The strengthening was investigated at either tension or compression zone. RECC was developed with crumb rubber and powder rubber. RECC showed excellent performance for shear strengthening and cracking resistance. A new model was proposed to predict the shear strength of fibrous concrete beams with no stirrups. Abstract: This study evaluated the shear behavior of lightweight self-consolidating concrete (LWSCC) beams strengthened with rubberized engineered cementitious composite (RECC). The RECC in this investigation, was developed with crumb RECC (CRECC) or powder RECC (PRECC). Four reinforced LWSCC beams layered with either CRECC or PRECC at the tension or compression zone, were constructed with no stirrups and tested in shear. Another three beams fully cast with LWSCC, CRECC, and PRECC, were tested for comparison. The performance of all tested beams was evaluated through different aspects including cracking behaviour, failure modes, ultimate shear load, post-diagonal cracking resistance, deformability, and energy absorption capacity. The experimental results indicated that strengthening LWSCC beams with either a CRECC or PRECC layer improved their ultimate shear strength, deformability, and energy absorption capacity without significant increase in their self-weight. The highest improvement in the shear behavior of the LWSCC beams was recorded when the CRECC or PRECC layer was located at the compression zone. Meanwhile, placing the RECC layer at the tension zone helped to enhance the cracking resistance, which indicates better protection for tensile reinforcing bars. The results also indicated that powder rubber seemed to be more efficient in developing RECC with higher fresh and mechanical properties compared to crumb rubber. The shear capacity of the tested composites was successfully estimated using a new model proposed based on a modification of the Eurocode's equation.